Health care system factors influencing primary healthcare workers' engagement in national cancer screening programs: a qualitative study. (23rd June 2022) - Verbunt, Ebony; Boyd, Lucy; Creagh, Nicola; Milley, Kristi; Emery, Jon; Nightingale, Claire; Kelaher, Margaret
Abstract: Objective : This study aimed to explore factors across the environment, organisation and care team levels of the health care system that influence the engagement of primary healthcare workers (PHCWs) in Australia's national cancer screening programs. Methods : A cross‐sectional qualitative study involving semi‐structured interviews with PHCWs – general practitioners (n=10), practices nurses (n=10), and practice managers (n=10) from settings across Australia. Transcripts were analysed using the Framework Method. Results : Two environment‐level factors were found to influence several organisation and care team level factors. Firstly, the financial structure of primary health care, impacting on practitioner: time, practice culture, screening knowledge and opportunistic conversations. Secondly, the structure of screening programs had flow‐on effects for: access to patient screening records, recall and reminder systems, and sense of program ownership. Conclusions : Encouraging more effective PHCW engagement in the screening programs requires the consideration and mitigation of overarching financial and structural barriers. Up‐to‐date and easy‐to‐use recall and reminder systems, whole‐of‐practice approaches which optimise the role of each PHCW and the identification of a 'champion' to drive implementation should be considered. Implications for public health : This study offers insights into what elements practice and practitioner targeted initiatives in Australia should incorporate, potentially leading to improved engagement of PHCWs and increased cancer screening participation rates.